2017
DOI: 10.1007/s11103-017-0651-3
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of gene expression in maize leaves treated with low temperature. II. Combined effect of severe cold (8 °C) and circadian rhythm

Abstract: numerous genes lacking circadian rhythm responded to the cold by undergoing up-or down-regulation. Notably, the transcriptome changes preceded major physiological manifestations of cold stress. In silico analysis of metabolic processes likely affected by observed gene expression changes indicated major down-regulation of photosynthesis, profound and multifarious modulation of plant hormone levels, and of chromatin structure, transcription, and translation. A role of trehalose and stachyose in cold stress signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 76 publications
(106 reference statements)
0
17
0
Order By: Relevance
“…Some salt stress-responsive genes, such as SOS1 , RD29A and DREB2A , exhibit a 24-h period of expression in Arabidopsis , suggesting that salt tolerance may also be affected by the circadian clock (Park et al, 2016a ). In some cases, other stress, such as cold and drought, modifies the transcription pattern of a major portion of genes showing diurnal oscillation (Wilkins et al, 2010 ; Jończyk et al, 2017 ). Resent evidence indicates that plants respond to salt stress more strongly during the day than at night and salt-induced expression of RD29A and SOS1 was much higher in the daytime than at night (Park et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…Some salt stress-responsive genes, such as SOS1 , RD29A and DREB2A , exhibit a 24-h period of expression in Arabidopsis , suggesting that salt tolerance may also be affected by the circadian clock (Park et al, 2016a ). In some cases, other stress, such as cold and drought, modifies the transcription pattern of a major portion of genes showing diurnal oscillation (Wilkins et al, 2010 ; Jończyk et al, 2017 ). Resent evidence indicates that plants respond to salt stress more strongly during the day than at night and salt-induced expression of RD29A and SOS1 was much higher in the daytime than at night (Park et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…Five studies reporting over 1,000 DEGs each, carried out on an aggregate of nine inbred lines, formed the core set of projects analysed here ( Fernandes et al, 2008 ; Sobkowiak et al, 2014 ; Jończyk et al, 2017 ; Lu et al, 2017 ; Waters et al, 2017 ; Table S1 ). Among them the reference study ( Sobkowiak et al, 2014 ) investigated two lines and found almost 8,000 genes changing expression in at least one line.…”
Section: A Search For Key Cold-affected Maize Genesmentioning
confidence: 99%
“…Conversely, most non-genetic sources are due to macro-environmental fluctuations resulting from resource availability during crop lifetime (Shelford, 1931). Despite this unfolded division, the effect of the environment on shaping gene expression (e.g., Plessis et al, 2015;Jończyk et al, 2017;Liu et al, 2020) and fine-tuning epigenetic factors (Varotto et al, 2020;Vendramin et al, 2020) creates an indissoluble envirotype-phenotype covariance in the phenotypic records (Lynch and Walsh, 1998). Thus, for any genotype-phenotype association study across multiple environments (e.g., mapping quantitative trait loci, QLT; genomic association studies, GWAS), there is a strong non-genetic influence that can be better understood using envirotypingbased data, i.e., a foundation of multiple techniques to collect, process, and integrate environmental information in genetic and genomic studies, Costa-Neto et al (2020a).…”
Section: Introductionmentioning
confidence: 99%